THE IMPACT OF FOREIGN WORKER RESTRICTIONS ON FOREIGN DIRECT INVESTMENT (FDI) REALIZATION IN INDONESIA - Dahlan; Henry Aspan; Etty Sri Wahyuni; Muhammad Juang Rambe (International Conference on Health Science, Green Economics, Educational Review and Technology, 2025)
Indonesia has experienced significant growth in foreign direct investment (FDI) inflows, reaching USD 47.5 billion in 2023 and exceeding the target of IDR 1,714 trillion in 2024. However, strict foreign worker regulations potentially affect the investment decisions of multinational companies. This research aims to analyze the impact of foreign worker restrictions on FDI realization in Indonesia with a case study in North Sumatra Province. The research method uses a qualitative approach with regulatory analysis and secondary data. The results show that although foreign worker restrictions through Government Regulation Number 34 of 2021 and Minister of Manpower Regulation Number 8 of 2021 aim to protect local workers and encourage technology transfer, these policies create trade-offs against Indonesia's investment attractiveness. Requirements such as mandatory local counterparts, Foreign Worker Utilization Compensation Fund (DKPTKA), and position restrictions create additional costs for investors. The Omnibus Law on Job Creation has simplified licensing procedures, but implementation challenges remain, particularly in regions like North Sumatra. The research recommends a balance between local workforce protection and investment facilitation through more flexible sector-based regulatory reforms.